Associations between single nucleotide polymorphisms in iron-related genes and iron status in multiethnic populations. - Christine E McLaren; Stela McLachlan; Chad P Garner; Chris D Vulpe; Victor R Gordeuk; John H Eckfeldt; Paul C Adams; Ronald T Acton; Joseph A Murray; Catherine Leiendecker-Foster; Beverly M Snively; Lisa F Barcellos; et al. (PLoS ONE)
The existence of multiple inherited disorders of iron metabolism suggests genetic contributions to iron deficiency. We previously performed a genome-wide association study of iron-related single nucleotide polymorphisms (SNPs) using DNA from white men aged ≥ 25 y and women ≥ 50 y in the Hemochromatosis and Iron Overload Screening (HEIRS) Study with serum ferritin (SF) ≤ 12 µg/L (cases) and controls (SF >100 µg/L in men, SF >50 µg/L in women). We report a follow-up study of white, African-American, Hispanic, and Asian HEIRS participants, analyzed for association between SNPs and eight iron-related outcomes. Three chromosomal regions showed association across multiple populations, including SNPs in the TF and TMPRSS6 genes, and on chromosome 18q21. A novel SNP rs1421312 in TMPRSS6 was associated with serum iron in whites (p = 3.7 × 10(-6)) and replicated in African Americans (p = 0.0012).Twenty SNPs in the TF gene region were associated with total iron-binding capacity in whites (p<4.4 × 10(-5)); six SNPs replicated in other ethnicities (p<0.01). SNP rs10904850 in the CUBN gene on 10p13 was associated with serum iron in African Americans (P = 1.0 × 10(-5)). These results confirm known associations with iron measures and give unique evidence of their role in different ethnicities, suggesting origins in a common founder.